The Spiritual Distress of Adolescents "Men Sex Men"(MSM) Infected with HIV in Bandung - Aisyah, Popy Siti; Lusiani, Eli; Widiayanti, Anggriyana Tri (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
ABSTRACTIntroduction: The prevalence of cases of HIV infection in the group of adolescents “Men Sex Men (MSM) in Indonesia has continued to increase from 2015 to 2019. The problem of decreasing physical health, feeling depressed, social stigma, stress and inconsistent behavior with religious values will create prolonged distress that hinders the quality of life. Objectives: The purpose of this study was to identify spiritual distress in adolescents infected with HIV with MSM. Methods: This study was conducted with a cross-sectional approach to 84 young people living with HIV/AIDS. The sample selection technique used snowball sampling with a Spiritual questionnaire. Data analysis was conducted by using frequency distribution and Lambda test processed using a computer system. Results: The results showed that 56% were in a state of spirituality with no disturbance, 38.1% were in moderate spiritual distress, and 6% were severe spiritual distress. The SSI score mean of respondents was 16.3 ± SD 4.9. There was a correlation between the length of diagnosis and the incidence of spiritual distress with a p-value of 0.000 and a value of r = 0.459. Spiritual distress tended to occur a lot in the early days of being diagnosed with HIV. There was no correlation between age and the incidence of spiritual distress (p = 0.097). Discussion: This study showed that spiritual care support for adolescents MSM would help overcome existential problems related to HIV.ABSTRAKPendahuluan : Prevalensi kasus infeksi HIV pada kelompok remaja dengan  Lelaki seks sesama Lelaki (LSL) di Indonesia terus mengalami peningkatan dari tahun 2015 – 2019. Permasalahan penurunan kesehatan fisik, perasaan tertekan, stress stigma sosial serta pertentangan perilaku dengan nilai- nilai agama akan menjadikan distress berkepanjangan yang menghambat peningkatan kualitas hidupnya. Tujuan : Tujuan penelitian ini adalah untuk mengidentifikasi distress spiritual pada Remaja terinfeksi HIV dengan LSL. Metode : Penelitian ini dilakukan dengan pendekatan cross sectional terhadap 84 remaja ODHA LSL. Tehnik pemilihan sampel menggunakan snowball sampling dengan kuesioner Spiritual Scale Injury. Analisis data menggunakan distribusi frekuensi dan Uji lambda yang diolah menggunakan sistem komputer. Hasil: Hasil penelitian menunjukkan 56 % berada pada kondisi spiritualitas tidak ada gangguan, 38,1 % menunjukkan distress spiritual sedang dan 6 % menunjukkan distress spiritual berat. Rata-rata skor SSI responden mean 16,3 ± SD 4.9.  Terdapat  korelasi antara lama terdiagnosa dengan kejadian distress spiritual dengan nilai p 0,000 dan nilai r = 0,459. Distress spiritual cenderung banyak terjadi pada awal awal terdiagnosa HIV. Tidak ada korelasi antara usia dengan kejadian distress spiritual (p=0,097). Diskusi : Penelitian ini menunjukkan bahwa dukungan spiritual care pada remaja LSL akan membantu mengatasi masalah eksistensial berkaitan dengan HIV.